2009
DOI: 10.1177/0969733009102692
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Nurses' Attitudes To Euthanasia and Physician Assisted Suicide

Abstract: In this review of empirical studies we aimed to assess the influence of religion and world view on nurses' attitudes towards euthanasia and physician assisted suicide. We searched PubMed for articles published before August 2008 using combinations of search terms. Most identified studies showed a clear relationship between religion or world view and nurses' attitudes towards euthanasia or physician assisted suicide. Differences in attitude were found to be influenced by religious or ideological affiliation, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 33 publications
4
56
0
3
Order By: Relevance
“…From this perspective, a lot of literature has been written on the interplay between religious/ideological convictions and ethical attitudes with regard to euthanasia and assisted suicide. A considerable number of studies among health care professionals worldwide have shown an influence of (the intensity of) religious belief on the willingness to endorse euthanasia and assisted suicide (Ward and Tate 1994, Sorbye et al 1995, Bachman et al 1996, Di Mola et al 1996, Portenoy et al 1997, Grassi et al 1999, Willems et al 2000, Emanuel 2002, Ryynänen et al 2002, Sprung et al 2003, Cuttini et al 2004, Mü ller-Bush et al 2004, Miccinesi et al 2005, Rurup et al 2005, Sprung et al 2007a, 2007b, Cohen et al 2008, Gielen et al 2008, Gielen et al 2009b, Inghelbrecht et al 2009, Seale 2009). Likewise, studies among the general public have generally shown that endorsement of euthanasia and assisted suicide decreases as the intensity of religiosity increases (Genuis et al 1994, Caddell and Newton 1995, Achille and Ogloff 1997, MacDonald 1998, DeCesare 2000, Emanuel 2002, Ryynänen et al 2002, Burdette et al 2005, Rietjens et al 2005, Rurup et al 2005, Cohen et al 2006, Chong and Fok 2009.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this perspective, a lot of literature has been written on the interplay between religious/ideological convictions and ethical attitudes with regard to euthanasia and assisted suicide. A considerable number of studies among health care professionals worldwide have shown an influence of (the intensity of) religious belief on the willingness to endorse euthanasia and assisted suicide (Ward and Tate 1994, Sorbye et al 1995, Bachman et al 1996, Di Mola et al 1996, Portenoy et al 1997, Grassi et al 1999, Willems et al 2000, Emanuel 2002, Ryynänen et al 2002, Sprung et al 2003, Cuttini et al 2004, Mü ller-Bush et al 2004, Miccinesi et al 2005, Rurup et al 2005, Sprung et al 2007a, 2007b, Cohen et al 2008, Gielen et al 2008, Gielen et al 2009b, Inghelbrecht et al 2009, Seale 2009). Likewise, studies among the general public have generally shown that endorsement of euthanasia and assisted suicide decreases as the intensity of religiosity increases (Genuis et al 1994, Caddell and Newton 1995, Achille and Ogloff 1997, MacDonald 1998, DeCesare 2000, Emanuel 2002, Ryynänen et al 2002, Burdette et al 2005, Rietjens et al 2005, Rurup et al 2005, Cohen et al 2006, Chong and Fok 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they must realise that giving attention to a patient's religious or ideological identity may not be restricted to offering spiritual guidance. Indeed, religion and world view might play an important influential role in dealing with illness and making concrete medical decisions (at the end of life) (Carmel and Mutran 1997, Leichtentritt and Rettig 1999, Ejaz 2000, Musgrave et al 2001, Margalith et al 2003, Wenger and Carmel 2004, DeKeyser Ganz and Musgrave 2006, Coleman et al 2007, ColemanBrueckheimer et al 2009, Gielen et al 2009b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of literature has demonstrated the importance of religious beliefs in attitudes to these subjects both in terms of the strength of the religious affiliation e religiosity (Bachman et al, 1996;Baume et al, 1995;Jorgenson and Neubecker, 1980;Kalish, 1963;O'Neill et al, 2003;Suarez-Almazor et al, 1997;Ward, 1980), and in terms of the religious denomination with which one is affiliated (Anderson and Caddell, 1993;Caddell and Newton, 1995;O'Neill et al, 2003). Interestingly studies have shown that a majority of doctors in the UK oppose legalisation of physician assisted suicide and euthanasia and that their religiosity appears to affect their attitudes (McCormack et al, 2012), a finding echoed elsewhere (Gielen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies investigated the attitude of nurses about euthanasia. The results of some studies in Western countries, such as Belgium (7)(8)(9), Australia (10), and Sweden (11) showed that most nurses in these countries agreed with legalization of euthanasia. On one hand, some studies in Asian countries, especially Japan (12,13) and Malaysia (14) showed negative attitude of healthcare professionals, including nurses, about euthanasia.…”
Section: Introductionmentioning
confidence: 99%